Genome-wide association meta-analysis of functional outcome after ischemic stroke. (19th March 2019) - Söderholm, Martin; Pedersen, Annie; Lorentzen, Erik; Stanne, Tara M.; Bevan, Steve; Olsson, Maja; Cole, John W.; Fernandez-Cadenas, Israel; Hankey, Graeme J.; Jimenez-Conde, Jordi; Jood, Katarina; Lee, Jin-Moo; et al.
Abstract : Objective: To discover common genetic variants associated with poststroke outcomes using a genome-wide association (GWA) study. Methods: The study comprised 6, 165 patients with ischemic stroke from 12 studies in Europe, the United States, and Australia included in the GISCOME (Genetics of Ischaemic Stroke Functional Outcome) network. The primary outcome was modified Rankin Scale score after 60 to 190 days, evaluated as 2 dichotomous variables (0–2 vs 3–6 and 0–1 vs 2–6) and subsequently as an ordinal variable. GWA analyses were performed in each study independently and results were meta-analyzed. Analyses were adjusted for age, sex, stroke severity (baseline NIH Stroke Scale score), and ancestry. The significance level was p < 5 × 10 −8 . Results: We identified one genetic variant associated with functional outcome with genome-wide significance (modified Rankin Scale scores 0–2 vs 3–6, p = 5.3 × 10 −9 ). This intronic variant (rs1842681) in the LOC105372028 gene is a previously reported trans-expression quantitative trait locus for PPP1R21, which encodes a regulatory subunit of protein phosphatase 1. This ubiquitous phosphatase is implicated in brain functions such as brain plasticity. Several variants detected in this study demonstrated suggestive association with outcome ( p < 10 −5 ), some of which are within or near genes with experimental evidence of influence on ischemic stroke volume and/or brain recovery (e.g., NTN4, TEK, and PTCH1 ). Conclusions: In this large GWA study on functional outcome after ischemic stroke, we report one significant variant and several variants with suggestive association to outcome 3 months after stroke onset with plausible mechanistic links to poststroke recovery. Future replication studies and exploration of potential functional mechanisms for identified genetic variants are warranted.